How consumers view hospital advertising - Andaleeb, Syed Saad (© 1994 The Haworth Press, Inc., 2016)
This article was published in the Journal of Hospital Marketing [© 1994 by The Haworth Press, Inc. ] and the definite version is available at : http://doi.org/10.1300/J043v08n02_08 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1300/J043v08n02_08